Optimizing Construction Performance: The Essential Role of Quantity Surveyors and their Involvement in Heavy Engineering Projects - Akorah, C.; Agu, N. N.; Ajator, U. O.; Nwoyiri, C. S. (International Journal of Real Estate, 2025)
The success of projects is measured by the parameters of time, cost and quality. However, it is common knowledge in Nigeria that most Heavy Engineering construction projects have not performed well in each of these parameters. Quantity surveyors though present in engineering projects are underutilized in cost and time performance and project delivery process at the pre and post completion stage of the project. This research seeks to appraise the roles and level of involvement of quantity surveyors in heavy engineering projects delivery. A sample survey design was used for this investigation. The population for this study consists of Quantity Surveyors in Enugu and Anambra state. The sample of the study comprises 73 quantity surveyors in Enugu State and Anambra State. Simple random sampling technique was used to draw the sample. The research instrument used for this research is a questionnaire. It was administered using a set of predetermined questions. The data collected were analyzed using both descriptive and inferential statistics. The reliability test for this study was conducted using Cronbach’s coefficient Alpha, the alpha value derived from each objective indicates a figure greater than 0.7. The study reveals that quantity surveyors play a multifaceted and crucial role in heavy engineering projects in Southeast Nigeria. Their involvement extends beyond traditional cost management to encompass broader project oversight and value creation. The significant variation in involvement across project types suggests a need for a more standardized approach to QS integration in different heavy engineering contexts.